Persepsi dan Partisipasi Masyarakat Lokal terhadap Pemanfaatan dan Pengelolaan Kawasan-kawasan Cagar Alam Kabupaten Teluk Bintuni - Nicolaus Y. Leftungun; A.P.E. Widodo; Ludia T. Wambrauw (Program Pascasarjana Universitas Papua, 2021)
This study aims to determine the level of perception and participation of the community around the Bintuni Bay Nature Reserve area and to provide recommendations with active community involvement. This study was conducted in Korano Jaya SP2 and Banjar Asoy SP4 Villages, Manimeri District, Teluk Bintuni Regency. In this study, based on the excessive use of nature reserves, it requires the views of the community around the nature reserve area, the approach used to obtain information by means of interviews or Forum Group Discussion and analyzed using a Likert scale. The results of this study indicate that community participation in order to be involved in the management of the nature reserve area is very high, the lack of public knowledge of the nature reserve area makes people often use the area as a place to catch crabs, shellfish (The Locals called as Bia) and fish for sale, sometimes for consumption As a recommendation from the results of this study is to provide an understanding for the community about the preservation of nature reserves and formulate several strategies that can be used as a support for the community's economy and community involvement in the nature reserve area.